ASSESSMENT OF THE EPIDEMIOLOGICAL PICTURE OF DENTAL ANOMALIES AND DEFORMATIONS IN CHILDREN - Xalmanov B.A; Suvonov K. J; Ikramov G. A; Allanazarov O.T (Scholar Express Journals, 2024)
the analysis of the results of cephalometric examinations of 801 patients under the age of 18, who were diagnosed with teeth-jaw anomalies and deformities, is presented.
Keywords: Anomaly; deformity; anemia; endocrine diseases